THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND ANEMIA IN THE 2nd TRIMESTER PREGNANT WOMEN IN KAMPUNG LAUT INPATIENT HEALTH CENTER - Sari, Yesi Mustika (STIKES Syedza Saintika Padang, 2023)
Pregnant women who have less nutritional status with an upper arm circurnference <23,5 cm are at risk of anemia, anemia during pregnancy may be at risk of bleeding during labor and at risk of delivering a low birth weight baby. Thisstudy alms to determine the realationship between nutritional status of pregnant women with hemoglobin levels in pregnant women trimester II.This study uses an analytical survey method with a crossectional approach. This study uses technique sampling where the sample is the entire population, namely 37 trimester pregnant women, wich amounted to 37 people.This research was conducted at Puskesmas Rawat Inap Kampung Laut using observation sheets and tested with chi square.Nutritional status of pregnant women majority normal 22 respondents (59,5%), hemoglobin majority anemia anemia 24 respondents (64,9%), there is relationship between nutritional status and hemoglobin level in pregnant mother oftrimester II with indigo nilai p-value 0,008(p <0,005).Based on the result of this study, healt workers can provide healt education, especially the incidence of anemia in pregnant women and conducting discussing anemia problems using leaflets or brochures to facilitate repetition of information to pregnant.